Mechanical behavior of glass fiber-epoxy composite laminates for ship hull structures - Gunarti, Monika Retno; Prawoto, Agus; Fauzi, Wahyu Nur; Wirawan, Willy Artha (Mechanical Engineering for Society and Industry, 2024)
Polymer composite is widely used in various structures due to its strength-to-load ratio. Despite the significant benefits, many structures are vulnerable to high-impact loads in practical situations. Therefore, this research aimed to explore the effect of fiber arrangement on the mechanical behavior of glass fiber-epoxy composite laminates. Experiments were conducted on several samples with glass fiber arrays of Chopped Strand Matt (CSM), Woven Rovings (WR), and Woven Cloth (WC). The composite fabrication was molded using the vacuum pressure infusion (VAPRI) method. The mechanical behavior of laminate composite was obtained using a tensile test, tree point bending, shore D hardness, Charrpy impact, fracture observation, and fiber-matrix delamination. The results showed that WR arrangement excelled in various mechanical behaviors, including flexural strength 6992.6 Mpa, Hardnes 75.66 HD, and Impact 0.1789 J/mm. In comparison, the highest tensile strength value was obtained in the WC arrangement of 73.24 Mpa. This research showed that both regular and arranged fiber provided better mechanical properties than random fiber. The incorporation of fiber arrangement could be recommended in the further development of high-performance polymer composite.